Expectant treatment for angular pregnancy after assisted reproduction technology: a safe and patient-friendly treatment strategy - Yang, Peiwen; Shen, Lin; Ai, Jihui; Zhao, Yiqing (Frontiers in Medicine, 2023)
Introduction: Currently, the treatment strategies for angular pregnancy in the first trimester after assisted reproduction technology (ART) are unclear. Improper treatment will cause unnecessary losses to patients, especially infertile patients, after ART. The purpose of this study was to clarify the pregnancy outcomes of expectant treatment for angular pregnancy post-ART and to provide a basis for the formulation of clinical treatment strategies. Method: This retrospective case series study was performed at the Reproductive Medicine Center of a university hospital. Maternal data and pregnancy outcomes were collected and analyzed for all patients diagnosed with angular pregnancies after ART between January 2016 and August 2021. The outcomes included live birth, term birth, premature birth, early pregnancy loss, fetal death, placental abruption, uterine rupture, maternal death, and hysterectomy. Results: A total of 78 patients were analyzed in this study, of whom 54 (69.2%) had live births, 44 (56.4%) had term births, 21 (26.9%) had an early pregnancy loss, 1 (1.3%) had mid-trimester missed abortion, 1 (1.3%) underwent mid-trimester labor induction due to fetal malformation, and 1 (1.3%) underwent uterine rupture. There were no cases of maternal death, placental abruption, or hysterectomies. Discussion: Angular pregnancy after ART is not as dangerous as that described in previous studies; most cases could be treated expectantly under close-interval follow-up and obtain live birth.